2006
DOI: 10.1002/app.24884
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of hydrophilic nanocomposite coating on glass substrate

Abstract: Hydrophilic coatings based on 3-glicidoxy propyl trimethoxy silane (GPTMS) and polyethylene glycol (PEG) were prepared with the incorporation of tetramethoxysilane (TMOS) and silica nanoparticle colloidal suspension by a sol-gel process. Characterization of the coatings has been performed by Fourier Transform Infrared (FTIR) and Attenuated Total Reflectance Infrared (ATR-IR) techniques. Morphological properties were characterized by Scanning Electron Microscopy (SEM). The distribution of Si atoms in the hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Contact angle of water on the ABS-clay nanocomposite materials increased with respect to the increase in clay content. Several other reports on the wetting phenomena on the polymer nanocomposites appeared in the literature recently [17][18][19][20][21]. Here our aim was to study the wetting behaviour of the polystyrene/calcium phosphate nanocomposites with respect to water and methylene iodide.…”
Section: Introductionmentioning
confidence: 99%
“…Contact angle of water on the ABS-clay nanocomposite materials increased with respect to the increase in clay content. Several other reports on the wetting phenomena on the polymer nanocomposites appeared in the literature recently [17][18][19][20][21]. Here our aim was to study the wetting behaviour of the polystyrene/calcium phosphate nanocomposites with respect to water and methylene iodide.…”
Section: Introductionmentioning
confidence: 99%
“…[15] However, the treatment only slightly improved SU-8 adhesion on Pyrex at low exposure doses but it was still not possible to provide an acceptable processing window. Further effort of introducing chemical bonding using coupling agent GPTMS [16,17] did not show significant improvement either. This demonstrated that the surface adhesion was not the only issue that dictated the process.…”
Section: Resultsmentioning
confidence: 99%
“…These porous silicate matrices obtained by the low-temperature sol-gel method act as promising host matrix for the encapsulation of biomolecules [1,5]. So as a result, pore-size motif is one of the key elements which enables to accomplish the entrapment of wide range of bio-molecules and opens up different applications [40][41][42][43][44][45][46][47][48]. This work reports such potent core-shell mesoporous silicate entrapped peptide nanotubes for smart glass coating applications and to create new smart sensor electrodes.…”
Section: Introductionmentioning
confidence: 97%